Kepribadian, Lingkungan Keluarga dan Pendidikan Kewirausahaan terhadap Minat Berwirausaha Generasi Z Banyuwangi - Fikri Budi Berliawan; Akhmad Suharto; Wenny Murtalining Tyas (IPM2KPE, 2024)
This research aims to investigate the influence of personality, family environment, and entrepreneurship education on generation Z's entrepreneurial interest in Banyuwangi. The research method uses a quantitative approach by distributing questionnaires to respondents who are members of generation Z in the area. Data analysis was carried out using regression techniques to evaluate the extent to which these independent variables influence generation Z's interest in entrepreneurship. The research results show that personality, family environment and entrepreneurial education have a positive and significant influence on generation Z's interest in entrepreneurship in Banyuwangi. In conclusion, factors that can encourage interest in entrepreneurship in generation Z provide a basis for developing more effective education and training programs, as well as provide insight for policy makers to advance entrepreneurial potential among generation Z. Keywords: Entrepreneurship, Personality, Family Environment, Education